2010
DOI: 10.1080/00140139.2010.500404
|View full text |Cite
|
Sign up to set email alerts
|

UAV-guided navigation for ground robot tele-operation in a military reconnaissance environment

Abstract: A military reconnaissance environment was simulated to examine the performance of ground robotics operators who were instructed to utilise streaming video from an unmanned aerial vehicle (UAV) to navigate his/her ground robot to the locations of the targets. The effects of participants' spatial ability on their performance and workload were also investigated. Results showed that participants' overall performance (speed and accuracy) was better when she/he had access to images from larger UAVs with fixed orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…U.S. Air Force scientists (Chappelle, McMillan, Novy, & McDonald, 2010;Chappelle, Novy, Randall, & McDonald, 2010) interviewed 53 subject matter experts about abilities that were critical to effective performance of UAS control tasks in terms of piloting and sensor operations; SpA was identified as an important factor for both tasks. Our previous research showed that individuals with greater SpA exhibited more effective visual scanning and target detection performance (Chen, 2010;Chen & Joyner, 2009;Chen & Terrence, 2008.…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…U.S. Air Force scientists (Chappelle, McMillan, Novy, & McDonald, 2010;Chappelle, Novy, Randall, & McDonald, 2010) interviewed 53 subject matter experts about abilities that were critical to effective performance of UAS control tasks in terms of piloting and sensor operations; SpA was identified as an important factor for both tasks. Our previous research showed that individuals with greater SpA exhibited more effective visual scanning and target detection performance (Chen, 2010;Chen & Joyner, 2009;Chen & Terrence, 2008.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Spatial ability (SpA) has been found to be a significant factor in certain visual display domains (Stanney & Salvendy, 1995), multitasking involving flight asset monitoring and management (Morgan et al, 2011), virtual environment navigation (Chen, Czerwinski, & Macredie, 2000), target search task (Chen, 2010;Chen & Joyner, 2009;Chen & Terrence, 2008, and robotics task performance (Cassenti, Kelley, Swoboda, & Patton, 2009;Lathan & Tracey, 2002). U.S. Air Force scientists (Chappelle, McMillan, Novy, & McDonald, 2010;Chappelle, Novy, Randall, & McDonald, 2010) interviewed 53 subject matter experts about abilities that were critical to effective performance of UAS control tasks in terms of piloting and sensor operations; SpA was identified as an important factor for both tasks.…”
Section: Individual Differencesmentioning
confidence: 99%
“…They have also found signifant use by the military [19,20]. In "Low-Cost Aerial Unit for Outdoor Inspection of Building Facades" the authors used a UAS equipped with a Microsoft Kinect sensor in order to collect geometric data from buildings [7].…”
Section: Uas Applications In Surveying Sensing and Scanningmentioning
confidence: 99%
“…Rojo, Alczar, Lpez-Pichaco, & Nogales, 2003) and manipulators (Goertz, 1963;Howe & Kontarinis, 1994;D.-H. Kim, Kim, Kim, & Cha, 2001;C. Smith, Bratt, & Christensen, 2008) alike -through various input devices, from graphical interfaces (Paravati, Sanna, Lamberti, & Celozzi, 2011) to joysticks (C. H. Park & Howard, 2007) to motion capture (Hu, Meng, Liu, & Wang, 2003), and for various tasks, ranging from military reconnaissance (Chen, 2010;Kadous, Sheh, & Sammut, 2006) to telesurgery (Okamura, 2004) to caregiving at home (Labonte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%